Transformation of Electoral Regulations and Substantive Democracy in Post Reform Indonesia - Puadi, Puadi; Bachtiar, Bachtiar; Wicaksono, Filipus Wahyu (GOVERNORS, 2025)
Since the 1998 Reform, Indonesia has experienced major changes in its electoral system. However, these changes have not always strengthened democracy in practice. This study aims to examine how the political elite's power has influenced the design and implementation of electoral regulations between 1999 and 2024. Using a qualitative and descriptive-analytical approach, the study draws on institutional theory and the concept of substantive democracy. Data were collected from laws, Constitutional Court decisions, and institutional reports. The findings show that regulations such as electoral thresholds have concentrated power among political elites, limiting political competition and leadership renewal. The open-list system encourages expensive, personality-driven campaigns, weakening accountability and party unity. The use of the noken system in Papua, though culturally affirming, challenges democratic values of equality and individual participation. Widespread vote buying reflects the persistence of patron-client politics. Additionally, the deaths of many polling officers in 2019 highlight the state’s failure to protect election workers. The study concludes that Indonesia’s electoral rules remain procedural and lack substance. Electoral reform is urgently needed to ensure fairness, transparency, and safety in future elections.